Preparation of PLGA-Coated Porous Silica Nanofibers for Drug Release - Meina Zhang; Jasmine Lidder; Mounib Bahri; Haifei Zhang (MDPI AG, 2022)
Fibrous materials have unique applications in drug release and biomedical fields. This study reports on the preparation of porous silica nanofibers, using organic nanofibers as templates, and their use for drug release. Different from the commonly used electrospinning method, the organic nanofibers are produced via a self-assembly approach between melamine and benzene-1,3,5-tricarboxylic acid. Silica is then coated on the organic nanofibers via homogenization in a silica sol, a freeze-drying process, and then a sol-gel process. In order to regulate the surface area and mesopore volume of silica nanofibers, cetyltrimethyl ammonium bromide at different concentrations is used as template in the sol-gel process. With the removal of organic nanofibers and the surfactant by calcination, porous silica nanofibers are generated and then assessed as a scaffold for controlled drug release with ketoprofen as a model drug. Poly (D, L-lactide-co-glycolide) is coated on the silica nanofibers to achieve slow burst release and prolonged cumulative release of 25 days. This study demonstrates an effective method of preparing hollow silica nanofibers and the use of such nanofibers for long-term release with high drug loading.